2014
DOI: 10.1007/s12272-014-0522-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a double-coated probiotic formulation on functional constipation in the elderly: a randomized, double blind, controlled study

Abstract: A randomized, double blind, controlled study was conducted to evaluate a multi-species probiotic product, Duolac(®) Care, for the efficacy in functional constipation of elderly nursing home residents. Forty participants were randomly assigned to receive either one capsule containing six bacterial strains (2.5 × 10(8) viable cells/capsule) doubly coated with proteins and polysaccharides (DC group) or one capsule containing the same bacterial strains without the coating layers outside the cell (NC group) twice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 16 publications
1
6
1
3
Order By: Relevance
“…However, it is important to note that 30% of the participants in our study noticed a transient change in their defecation frequency. This finding is considered a normal reaction because some strains of Lactobacillus species increase the bowel movement frequency in adults as reported also in other studies [16][17]. Furthermore, our study showed both constipation and diarrhea were reported in a few cases without significance, whereas fever was not observed in any case during the period of probiotic consumption.…”
Section: The Study Participants' Compliance and Reported Symptomssupporting
confidence: 88%
“…However, it is important to note that 30% of the participants in our study noticed a transient change in their defecation frequency. This finding is considered a normal reaction because some strains of Lactobacillus species increase the bowel movement frequency in adults as reported also in other studies [16][17]. Furthermore, our study showed both constipation and diarrhea were reported in a few cases without significance, whereas fever was not observed in any case during the period of probiotic consumption.…”
Section: The Study Participants' Compliance and Reported Symptomssupporting
confidence: 88%
“…Only degree of straining differed significantly, declining with high-dose HN019 versus placebo at Day 28 in the BMF ≤ 3/week subpopulation; but, there were no differences in the changes from baseline to the end of the study between these groups. There are conflicting data on the typical baseline straining values for participants who are enrolled per Rome III criteria for functional constipation: studies have reported higher, 30 , 40 , 41 similar, 42 , 43 and lower 44 levels compared with us. However, our population was less constipated, according to the complete bowel emptying, abdominal pain, and bloating scores.…”
Section: Discussionmentioning
confidence: 77%
“…The resulting dysbiosis may be among the causes or the outcomes of opportunistic Enterobacteria proliferation, which seemed to positively correlate with enhancement in some pro-inflammatory signals (IL6 and IL8). Macfarlane 33 reported that short term symbiotic application could efficiently ameliorate the composition and metabolic functions of colonic bacterial communities and immune factors in old age people. Finally, Clarke and co-workers 34 showed a significant correlation between IL-6 and immune activation pathways.…”
Section: Discussionmentioning
confidence: 99%